MATN CRITICISM AND ITS ROLE IN THE EVALUATION OF HADITH AUTHENTICITY - Ayub, Ayub (IJISH (International Journal of Islamic Studies and Humanities), 2018)
For centuries, Muslim community has taken ‘ulūm al-ḥadīth for granted as a valid method in hadith verification; if a hadith is declared as an authentic hadith after examined using the method, then they will accept the hadith as an authentic one. Nevertheless, the traditional discipline has been criticised by various modern scholars who argue that traditional ‘ulūm alḥadīth is not a sufficient method to evaluate the authenticity of hadith reports. One of their reasons is that the traditional hadith criticism only examines the chain of narrations (sanad) of hadith reports and ignores the content (matn) of the hadith. This essay will discuss the role of matn criticism in the authentication of hadith; whether it is included in the traditional method of ‘ulūm al-ḥadīth or not, and if so, what is the criteria and how the scholars apply them.